The unique ecological role of pyrosomes in the Eastern Tropical Pacific. - Décima, M., M.R. Stukel, L. López-López & M.R. Landry (Limnology And Oceanography, 2019)
Pyrosomes are an important but often overlooked component of marine zooplankton communities, with limited existing information regarding their ecological and trophic roles in pelagic ecosystems. We present the first estimates of grazing and trophic interactions of the large tropical pyrosome, Pyrostremma spinosum, in the Eastern Tropical Pacific. While patchy in distribution, Pyrostremma spinosum's grazing impact was substantial, up to 17.5% of chlorophyll a standing stock d−1 in certain areas. In contrast, these organisms cleared a very small percentage of the abundant picoplankton Synechococcus spp. compared to the bulk zooplankton community. Stable isotopes (13C and 15N) indicated that particulate organic matter (POM) from the surface mixed layer (0–20 m) constitutes the isotopic food-web baseline for most of the zooplankton community, and zooplankton trophic interactions were size structured in some areas. Pyrosomes, doliolids, and appendicularians, along with the smallest size class of net-collected zooplankton, had isotopic values closest to pure herbivory, while intermediate size classes, copepods, and salps showed substantial omnivory/carnivory. Euphausiids, chaetognaths, and > 2 mm zooplankton were the main carnivorous zooplankton in the plankton food web. Stable isotopes indicated that Pyrostremma spinosum is trophically distinct from the rest of the zooplankton community, grazing just below the mixed layer (20–40 m), as opposed to feeding on surface POM. Pyrosomes represent an additional, distinct pathway for material transfer up the plankton food web, by directly consuming POM sources not substantially grazed upon by the rest of the mesozooplankton community.